The Potential Development of Dark Tourism in Goa Gudawang, Bogor Regency - Dinitri, Seruni; De Sember, Yohannes (Stupa, 2021)
Goa Gudawang is a natural cave site located in Bogor Regency. It was believed as a meditation by a number of warriors from the land of Pasundan and also often seen ’striped tigers’ who owned the pasundan land. The purpose of the study is to discover the potential development of dark tourism in Goa Gudawang. The methods used in this research are qualitative and quantitative method. The authors do direct exploration to the research site to get primary data regarding Goa Gudawang. Interviews and questioners were also conducted to Goa Gudawang Guards, local communities, Bogor Regency Culture and Tourism Office, and also visitors. In addition, the authors obtained data from literature related to research that is being done. The results found that Goa Gudawang has potential to become a dark tourism attraction as a dark exhibition. It has a symbol for dark tourism, but need more support from the local Government in order to make it as a dark exhibition. Nowadays, Goa Gudawawan is only focus on natural tourism. Its need added value to make it as special interest tourism especially for dark tourism. Moreover, Goa Gudawang only has one attraction to develop dark tourism, as a cave tourist usually uses it for meditation. But Goa Gudawang is rarely found in other places and has its own uniqueness for conducting dark tourism.